THE IMPORTANCE OF GRAMMAR IN TEACHING PROCESS. - Jumaboeva, Adolat (Журнал иностранных языков и лингвистики, 2021)
"Grammar is the structural foundation of our ability to express ourselves. The more we are aware of how it works, the more we can monitor the meaning and effectiveness of the way we and others use language. It can help foster precision, detect ambiguity, and exploit the richness of expression available in English." The teaching of grammar continues to be a matter of controversy in the field of Applied Linguistics and Second Language Acquisition . Grammar is an important aspect of language learning. Therefore, learning English is an important point to practice English correctly. This paper aimed to highlight the importance of grammar in language teaching process.